TINJAUAN YURIDIS PERLINDUNGAN KONSUMEN MENGENAI PENJUALAN PRODUK MAKANAN YANG TIDAK BERLABEL HALAL MENURUT UU NO 8 TAHUN 1999 - Egy Pratama; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
Indonesia is a country with a majority Muslim population. Food is one of the most necessary needs for humans to survive so that everyone is expected to pay more attention to the food products that will be consumed. In Islamic teachings there is an order to consume halal food and a prohibition to consume food that is haraam. Halal products are products that meet the requirements of halal in accordance with Islamic law ranging from the substance, the process and storage and presentation. This study aims to find out a juridical review of Consumer Protection regarding the sale of food products that are not labeled halal according to Law No. 8 of 1999. Consumer protection guarantee against the circulation of halal-labeled food products is guaranteed according to the prevailing laws and regulations and products labeled officially halal has provided a guarantee of legal certainty against the halal product itself which can be seen from the authority given by the government to MUI and BPJPH.